(untitled) (Third Sector Social Economic Review, 2019)
Today, we have been facing the cigarette as a crucial health issue in both developed and developing countries. Smoking is the most important cause of preventable disease and death. Stopping smoking is a significant behaviour change for the individual and his / her environment. Some of smokers have been attempting to stop smoking. But, most of it results in failure. Assesment of the factors affecting smoking cessation process is important in terms of planning successful smoking cessation attempts. Countries appeal to different practices such as tax increase, legal regulations and advertising ban so as to be able to reduce cigarette consumption. Social campaigns to create broad reactions, have been carried out by the states in order that some certain ideas can be adopted to the society and some necessary changes can be made in the patterns of thoughts and behavior. However, it is an important event to be able to question the effectiveness of the fact that these practices reach how much of the society and being able to learn the reflections in the society. In this study, the effects of demarketing practices on reducing the use of the state were investigated. As a result of this research, it was determined that consumers’ attitudes towards smoking were collected under 3 factors (perceived psychological value, perceived social value and perceived concentration value).In the research, it was determined that there was a significant relationship between the state’s strategies to reduce smoking and perceived psychological and concentration values of the consumers. As another result, too, it was concluded that as the age increases, the attitudes of consumers towards smoking decrease in the correlation analysis done.